(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Working environment has changed in the last few years and work has become more intensive i.e. demand for maximum attention and concentration, workload adaptions with the mental and physical abilities of human, solvation of various organising issues. Risk factors of working environment can be found in every profession and may affect a large number of employees. One of the essential issues in wood processing is noise presence during machining, which is why noise level determination at the workbench during whole working day is important thing to do. Measuring devices of the noise level are with various technological abilities, from which one need to choose the most appropriate for the particular situation. Some of the devices are or may be equipped with data recorder, which allows to save measured data for subsequent computer assessment. The article analyses Latvian legislation concerning the noise level determination in the workplace as well as allowable limits. The article offers simplified means of the noise measurement and registration abilities.